2004
DOI: 10.1111/j.1365-2141.2004.05286.x
|View full text |Cite
|
Sign up to set email alerts
|

Molecular mechanisms whereby immunomodulatory drugs activate natural killer cells: clinical application

Abstract: Summary Thalidomide and immunomodulatory drugs (IMiDs), which target multiple myeloma (MM) cells and the bone marrow microenvironment, can overcome drug resistance. These agents also have immunomodulatory effects. Specifically, we have reported that thalidomide increased serum interleukin‐2 (IL‐2) levels and natural killer (NK) cell numbers in the peripheral blood of responding MM patients. In this study, we investigated the mechanisms whereby IMiDs augment NK cell cytotoxicity. NK cytotoxicity and antibody‐de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
219
2
3

Year Published

2007
2007
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 299 publications
(229 citation statements)
references
References 54 publications
5
219
2
3
Order By: Relevance
“…As shown previously by other investigators, IMiDs have direct anti-myeloma effects and can overcome resistance to conventional therapy (Hideshima et al, 2000). It was demonstrated that in multiple myeloma, IMiDs increase the NK-cell pool by triggering the release of IL-2 secretion by T (Hayashi et al, 2005). There is evidence to support that lenalidomide enhances the expansion of NK and T cells in patients with multiple myeloma and that cells activated in the presence of lenalidomide secrete IFN-c (Chang et al, 2006).…”
Section: Discussionmentioning
confidence: 88%
“…As shown previously by other investigators, IMiDs have direct anti-myeloma effects and can overcome resistance to conventional therapy (Hideshima et al, 2000). It was demonstrated that in multiple myeloma, IMiDs increase the NK-cell pool by triggering the release of IL-2 secretion by T (Hayashi et al, 2005). There is evidence to support that lenalidomide enhances the expansion of NK and T cells in patients with multiple myeloma and that cells activated in the presence of lenalidomide secrete IFN-c (Chang et al, 2006).…”
Section: Discussionmentioning
confidence: 88%
“…This confirms previous observations of activation of NK and T cells after therapy with thalidomide or lenalidomide. 14,15 This immunostimulating effect of lenalidomide might be an important mechanism of its anti-myeloma activity beside its anti-angiogenetic properties and its apoptotic effect. The increase of T-regulatory cells in myeloma patients remains unclear, 16 and after allo-SCT, Tregulatory cells seem to have a GVHD-protecting effect.…”
Section: Discussionmentioning
confidence: 99%
“…It is important to understand that the induction of tumour cytotoxicity can also be a result of an enhanced immunological responses caused by IMiDs. The increased proliferation of a number of immune cell groups, including CD4-positive and CD8-positive cells in addition to the initiation of dendritic cell function, can lead to the activation of natural killer cells that drive cytophagy and cytolysis (Davies et al, 2001;Hayashi et al, 2005;Wu et al, 2008).…”
Section: Discussionmentioning
confidence: 99%